Developing Design Solutions for Smart Homes Through User-Centered Scenarios - Kim, Mi Jeong; Cho, Myung Eun; Jun, Han Jong (Frontiers in Psychology, 2020)
Abstract The success of smart homes is fundamentally dependent on their adoption and use by people in the context of daily life. This study investigated ways to control and adapt the technology to fulfill user daily needs, which are the active drivers of smart housing technology adoption. A framework of smart home services was developed by focusing on the practicability of each variable from the perspective of supporting user experience. By developing scenarios based on previous studies, we identified residents’ behaviors and intentions regarding smart home technology and its use. Their issues were identified through the health problems and daily activities identified in the scenarios, and customized smart home services were developed for each resident based on technical solutions, space requirements, and design solutions. The main strength of this study is the adoption of user-centered methods to build a rich picture of the issues that affect households and the community related to the design, installation, and use of technology.